Du “je” à l’impersonnel poétique et vice versa: L’acteur entre le personnage, le performeur et le témoin - Beaufils, Eliane (Mimesis Journal, 2013)
Actors of performances and of postdramatic theatre navigate commonly nowadays between the performer and the character. But what happens when the possibility of incarnation is completely denied, without offering the possibility of performing actions, of engaging personality? We think that the actor becomes an “experiencer”, a witness of all of us, who allows us to develop a very personal relation to the life on stage and to the words. We would like to focus on two main examples. In the Earthquake of Chili (2012), Chétouane’s actors just “speak” Kleist’s text; the sparing activity doesn’t illustrate the narration. But the actors say the text with their affection, they are moved by the text and themselves, becoming witnesses of a human reader, of impersonal empathy. Not only this aesthetic in absentia can be fulfilling acting. On the other hand, Pollesch’s actors contribute to make a highly intensive and intellectual text with the author and director, but Pollesch doesn’t permit them to project themselves in it. That’s why they are simultaneously so intensively dived in the text and absent from it, performing nothing but what is around the words, in deep af-fection and formality: witnesses of the struggle to think, to speak, to be.